Is oral health literacy associated with conceptions of care and behavior related to the prevention of COVID-19? - Luciana Reichert da Silva ASSUNÇÃO; Paula Dresch PORTELLA; Fabian Calixto FRAIZ; Mariane Carolina Faria BARBOSA; Larissa Chaves Morais de LIMA; Amanda Palmela PINHEIRO; Ana Flávia GRANVILLE-GARCIA; Fernanda de Morais FERREIRA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of the present study was to investigate the impact of oral health literacy (OHL) on conceptions of care and behaviors related to COVID-19. The sample came from two preliminary cross-sectional studies that determined the level of OHL of parents/guardians of six-to-12-year-old children in two major Brazilian cities (Curitiba and Belo Horizonte). Functional OHL was measured using the Brazilian version of the Rapid Estimate of Adult Literacy in Dentistry (BREALD-30) and the Health Literacy Dental Scale (HeLD-14) for the evaluation of interactive OHL. Participants were recruited through e-mail, social media, and telephone contact. The questionnaire on conceptions of care and behaviors related to COVID-19 was created based on the guidelines of the World Health Organization. Two hundred nineteen individuals participated in the study. There was no significant difference in socioeconomic and demographic variables and in the medians of BREALD and HeLD-14 between the two cities (P>0.05). Higher levels of functional OHL were associated with an appropriate conception that individual care affects collective care (P=0.038), but with an inappropriate conception of seeking medical assistance in cases of mild symptoms (P=0.030). Higher levels of interactive OHL were related to social distancing behavior in the city of Curitiba (P=0.049) and in the overall sample (P=0.040). It is concluded that functional OHL was associated with two of the investigated conceptions about COVID-19, while interactive OHL was associated with social distancing behavior. These data may suggest that different dimensions of the OHL can have an impact on different aspects of coping with the pandemic.